Increased mitochondrial fusion in a autosomal recessive CMT2A family with mitochondrial GTPase mitofusin 2 mutations. Issue 4 (7th December 2016) - Codron, Philippe; Chevrollier, Arnaud; Kane, Mariame S.; Echaniz‐Laguna, Andoni; Latour, Philippe; Reynier, Pascal; Bonneau, Dominique; Verny, Christophe; Procaccio, Vincent; Lenaers, Guy; Cassereau, Julien
Abstract: Charcot‐Marie‐Tooth type 2A disease (CMT2A) is an inherited peripheral neuropathy mainly caused by mutations in the MFN2 gene coding for the mitochondrial fusion protein mitofusin 2. Although the disease is mainly inherited in a dominant fashion, few cases of early‐onset autosomal recessive CMT2A (AR‐CMT2A) have been reported in recent years. In this study, we characterized the structure of the mitochondrial network in cultured primary fibroblasts obtained from AR‐CMT2A family members. The patient‐derived cells showed an increase of the mitochondrial fusion with large connected networks and an increase of the mitochondrial volume. Interestingly, fibroblasts derived from the two asymptomatic parents showed similar changes to a lesser extent. These results support the hypothesis that AR‐CMT2A‐related MFN2 mutations acts through a semi‐dominant negative mechanism and suggest that other biological parameters might show mild alterations in asymptomatic heterozygote AR‐CMT2A patients. Such alterations could be useful biomarkers helping to distinguish MFN2 mutations from variants, a growing challenge with the advent of next generation sequencing into routine clinical practice.